Polyherbal Soap - Unveiling Formulation Techniques and Quality Assessment Methods (International Journal of Scientific Research in Science and Technology, 2024)
Polyherbal soaps, a fusion of diverse botanicals, epitomize natural skincare. This article delves into their creation and meticulous quality assessments, spotlighting their relevance in modern skincare. The formulation process unveils a symphony of botanical contributions, like neem, turmeric, and aloe vera, enriching these soaps. Crafting these soaps involves artful techniques, from precision in the cold process to strategic additives amplifying their skin-nurturing effects. Evaluations ensure sensory allure and safety, employing chromatography to reveal skin-enhancing compounds and rigorous microbiological tests affirming efficacy against harmful agents. These soaps excel in acne care, hydration, and soothing effects. Challenges in consistency and compliance persist, yet the future promises ongoing innovation, bolstering their significance in skincare. This exploration invites all to discover polyherbal soaps, where nature meets scientific scrutiny for a holistic skincare journey.